HAK DAN KEDUDUKAN PEREMPUAN DALAM HUKUM KELUARGA (Studi Atas Pemikiran Feminisme Amina Wadud) - Fahmi Assulthoni; Farida Yuniati; Nuri Herachwati (Ulumuna: Jurnal Studi Keilsman, 2022)
Amina Wadud as a feminist activist is considered to widen the context of gender equality for women on the one hand. But on the other hand, she is labelled as having made a "new interpretation" of the Qur'anic texts relating to women. Her thinking and understanding eventually had an impact on the position of women in the context of family law. Where a woman has equality that is not much different from a husband. The study in this paper wants to know the extent of Amina Wadud's thoughts on the rights and position of women as wives. The study method used is descriptive qualitative with documentation data collection. Based on the results of the discussion and data findings, it can be concluded that every woman regardless of status has equal rights and position in family law. A woman as a wife is given the same opportunities such as filing for divorce, working, prohibiting her husband from polygamy, inheritance rights, testimony and so on. The gender equality offered by him lies in the position of men and women who are in the same condition or situation in order to fulfil their needs. Keywords: women's rights and position, family law, Amina Wadud